Deletion of a polyketide synthase phoE induces monoterpenes production in ascidian-derived fungus Diaporthe sp. SYSU-MS4722 - Yuan, Siwen; Zhuang, Shitao; Han, Yanhong; Wen, Yuhang; Chen, Senhua; Liu, Lan; Lin, Qifeng; Yan, Yan; Gao, Zhizeng; Wu, Qilin (Frontiers in Microbiology, 2025)
Marine-derived fungi represent an underexplored source of monoterpenes, with only sporadic reports over the past two decades, making their discovery particularly challenging. Whole-genome sequencing of Diaporthe sp. SYSU-MS4722, an ascidian-derived fungus isolated from Styela plicata, identified 130 biosynthetic gene clusters (BGCs), underscoring its vast biosynthetic potential. However, previous studies demonstrated that Diaporthe sp. SYSU-MS4722 predominantly produces xanthone phomoxanthone A under standard laboratory conditions, suggesting that many BGCs remain cryptic. Notably, 16 of these BGCs encode terpene synthase genes, indicating the potential for monoterpene biosynthesis. To activate these silent BGCs and discover monoterpenes, we deleted the polyketide synthase (PKS) gene phoE, responsible for phomoxanthone A biosynthesis, generating the mutant strain Diaporthe sp. SYSU-MS4722ΔphoE, from which three new monoterpenes, diaporterpenes D-F (1-3), three known monoterpenes (4-6), and two new polypropionate derivatives, diaporpolypropionate A (7) and diaporpolypropionate B (8), were isolated. Compounds 1, 4, 7, and 8 were evaluated for their cytotoxicity and anti-inflammatory effects in human non-small cell lung cancer A549 cells. Compound 1 exhibited cytotoxic activity with an IC50 value of 89.33 μM. Compounds 4 and 7 demonstrated anti-inflammatory activity, as measured by an ELISA assay assessing the inhibition of IL-6 secretion, with EC50 values of 41.85 μM and 70.80 μM, respectively. These results underscore genome mining as a powerful tool in natural product discovery and the exploration of novel chemical space from marine fungal resources.